The Collapse of Civilization and Beyond: A Socio-Political Study of Mary Shelley’s The Last Man - Kamal Mustafa, Hawar; Zainalddin Mohammed , Rebwar (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
This paper which is titled “The Collapse of Civilization and Beyond: A Socio-Political Study of Mary Shelley’s The Last Man,” is about a dystopian world created by an incurable plague. The aim of the paper is to show how the apocalypse is at the core of her work. Shelley’s prediction of the collapse of civilization as demonstrated in her text represents an original approach to her personal and political struggles, this approach detaches her from others, therefore, making her form a new literary genre. This paper uses the critical analysis approach to achieve its conclusion. It criticizes the ideas and beliefs of civilizations that have been established by human beings throughout the ages and cannot be irradicated. It analyses Mary Shelley’s The Last Man to critique this narrow-minded belief and demonstrate aspects that resulted in the collapse of civilization.